Real-World First-Line Treatment Patterns and Outcomes in Hormone Receptor-Positive Advanced Breast Cancer Patients: A Multicenter, Retrospective Study in China - Chen, Zhanhong; Ouyang, Quchang; Wang, Yongsheng; Wang, Junsheng; Wang, Haixue; Wu, Xiaohong; Zhang, Peili; Huang, Jian; Zheng, Yabing; Cao, Wenming; Shao, Xiying; Xie, Ning; et al. (Frontiers in Oncology, 2022)
Background: Recent data on first-line treatment patterns administered to hormone receptor-positive (HR+) advanced breast cancer (ABC) patients in the real-world setting are limited. This study aimed to report the first-line treatment patterns and outcomes of HR+ ABC patients in China. Methods: This was a multicenter, noninterventional study. Eligible patients were cytologically or histologically confirmed to have HR+ ABC with ≥2 complete medical records and received first-line therapies between January 2015 and June 2019. Treatment patterns and outcomes were extracted from structured or unstructured electronic medical records. Progression-free survival (PFS) was analyzed with the Kaplan-Meier method. Results: In total, 1072 patients with HR+ ABC were enrolled at 6 treatment sites: 327 human epidermal growth factor receptor 2-positive (HER2+) patients, 696 HER2-negative (HER2-) patients and 49 HER2-unknown patients. Overall, 62.41% of patients received first-line chemotherapy (CT), 21.08% received targeted therapy (TT) and 15.49% received endocrine therapy (ET). For HR+/HER2+ patients, 65.14% received TT, 28.44% received CT, and 5.81% received ET. Compared with patients who received TT, patients who received CT alone, had a significantly worse median PFS (adjusted hazard ratio [HR] =2.59, 95% confidence interval [CI], 1.64-4.10, p<0.001). For HR+/HER2- patients, 77.01% received CT, 20.69% received ET and 1.15% received TT. Compared with patients who received ET, patients who received CT with maintenance therapy had a significantly prolonged median PFS (adjusted HR =0.57, 95% CI, 0.44-0.76, p<0.001). Among HR+/HER2- patients who received CT with maintenance treatment, those with maintenance ET had a longer median PFS than those with maintenance CT, but the difference was not significant (adjusted HR=0.92, 95% CI, 0.64-1.33, p=0.66). Conclusions: This real-world study demonstrates that CT remains the mainstream first-line treatment option for HR+ patients in China. Among patients with HR+/HER2+ ABC, the majority received first-line TT and experienced a PFS benefit. A high percentage of HR+/HER2- patients received CT as first-line therapy in clinical practice. PFS benefit was significantly longer in patients who received CT with maintenance therapy. Moreover, there was no obvious difference in PFS between maintenance ET and CT. Maintenance ET may be a better choice considering its lower toxicity and better quality of life.